Waste Management Strategy in Developing Country: A Study Case of Waste Management Options in Kota Kinabalu Sabah, Malaysia - Mohammad Tahir Mapa; Aliakbar Gulasan; Nordin Sakke (Annals Of Faculty Engineering Hunedoara, 2010)
Much has been said in recent years about waste management policy, and recently the management of waste has found itself moving up the political agenda. The government is beginning to demonstrate some political leadership in its announcement of the Cabinet Office study into waste strategy. The need for change is more pressing than ever, and we are now in a position where we have to ensure that words become deeds. This research primarily focuses on the issues of sustainability and waste management in developing countries. For this study Malaysia is chosen as a country where waste management has become a major problem. Blessed with favorable natural resources, the Malaysia has traditionally been reliant on landfill sites as a low-cost waste disposal option. However, for the sake of intergenerational equity, such end-of-pipe solutions to the Malaysia's ever-increasing volumes of waste are unsustainable in the long-term. The challenge of moving towards a more resource efficient society is multifaceted and must be tackled on several levels. The result from the life cycle assessment analysis shows that depending on landfill alone are not sustainable in long term. Landfill must be cooperating with other method of waste management such as recycling or landfill with energy recovery.